Evidence for an Adult-Like Type 1-Immunity Phenotype of Vδ1, Vδ2 and Vδ3 T Cells in Ghanaian Children With Repeated Exposure to Malaria - León-Lara, Ximena; Yang, Tao; Fichtner, Alina Suzann; Bruni, Elena; von Kaisenberg, Constantin; Eiz-Vesper, Britta; Dodoo, Daniel; Adu, Bright; Ravens, Sarina (Frontiers in Immunology, 2022)
Effector capabilities of γδ T cells are evident in Plasmodium infection in young and adult individuals, while children are the most vulnerable groups affected by malaria. Here, we aimed at investigating the age-dependent phenotypic composition of Vδ1, Vδ2, and Vδ3 T cells in children living in endemic malaria areas and how this differs between symptomatic and asymptomatic Plasmodium falciparum infections. Effector capabilities of γδ T cells are evident in Plasmodium infection in young and adult individuals, while children are the most vulnerable groups affected by malaria. Here, we aimed to investigate the age-dependent phenotypic composition of Vδ1+, Vδ2+, and Vδ3+ T cells in children living in endemic malaria areas and how this differs between children that will develop symptomatic and asymptomatic Plasmodium falciparum infections. Flow cytometric profiling of naïve and effector peripheral blood γδ T cells was performed in 6 neonates, 10 adults, and 52 children. The study population of young children, living in the same malaria endemic region of Ghana, was monitored for symptomatic vs asymptomatic malaria development for up to 42 weeks after peripheral blood sampling at baseline. For the Vδ2+ T cell population, there was evidence for an established type 1 effector phenotype, characterized by CD94 and CD16 expression, as early as 1 year of life. This was similar among children diagnosed with symptomatic or asymptomatic malaria. In contrast, the proportion of type 2- and type 3-like Vδ2 T cells declined during early childhood. Furthermore, for Vδ1+ and Vδ3+ T cells, similar phenotypes of naïve (CD27+) and type 1 effector (CD16+) cells were observed, while the proportion of CD16+ Vδ1+ T cells was highest in children with asymptomatic malaria. In summary, we give evidence for an established adult-like γδ T cell compartment in early childhood with similar biology of Vδ1+ and Vδ3+ T cells. Moreover, the data supports the idea that type 1 effector Vδ1+ T cells mediate the acquisition of and can potentially serve as biomarker for natural immunity to P. falciparum infections in young individuals from malaria-endemic settings.